2013
DOI: 10.11144/javeriana.upsy12-3.bccc
|View full text |Cite
|
Sign up to set email alerts
|

Burden on Caregivers of Children with Cerebral Palsy: Predictors and Related Factors

Abstract: The main objective of this research was to explore which factors best predict the occurrence of burden on primary caregivers of children with cerebral palsy (CP). Understanding these factors enables the identification of those caregivers at risk of having their physical and psychological health adversely affected, and the implementation of intervention strategies to reduce the negative impact of caring on parents of children with chronic medical conditions. The study sample consisted of a total of 62 caregiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 52 publications
7
16
0
11
Order By: Relevance
“…Marrón et al assessed determinants of caregiver burden in a group of 62 mothers and fathers of children with CP and reported that the most important predictors of the burden include the degree of the child’s disability, depression and a sense of competence. Anxiety was not identified as a predictor of the burden [49]. This is consistent with the results reported by Ones et al who assessed 46 mothers of children with CP and 46 mothers of healthy children and did not find differences in the level of anxiety between the two groups.…”
Section: Discussionsupporting
confidence: 87%
“…Marrón et al assessed determinants of caregiver burden in a group of 62 mothers and fathers of children with CP and reported that the most important predictors of the burden include the degree of the child’s disability, depression and a sense of competence. Anxiety was not identified as a predictor of the burden [49]. This is consistent with the results reported by Ones et al who assessed 46 mothers of children with CP and 46 mothers of healthy children and did not find differences in the level of anxiety between the two groups.…”
Section: Discussionsupporting
confidence: 87%
“…Estos resultados son posibles de contrastar con otros estudios, respecto a la sobrecarga del cuidador de niños con discapacidad motora, los que de acuerdo a las características sociodemográficas se ha encontrado que más del 90% son mujeres y madres de los niños, y cerca de un 60% son casadas (Báez et al, 2009;Vaquiro & Stiepovich, 2010). La posibilidad de contar con redes de apoyo cercanas permite aliviar el nivel de sobrecarga de los cuidadores y fortalece el rol de la familia en la crianza del escolar con discapacidad (Marrón et al, 2013;Ortega et al, 2010;Rosenbaum, 2011;Vaquiro & Stiepovich, 2010). Sin embargo, no necesariamente asegura un rol compartido en el cuidado del escolar con discapacidad.…”
Section: Discussionunclassified
“…El estudio evidencia que los cuidadores de escolares con retos múltiples y discapacidad intelectual moderada poseen una mayor sobrecarga en comparación a los cuidadores de niños con discapacidad intelectual leve. El impacto y desgaste emocional que genera el estar a cargo de un niño con discapacidad intelectual moderada o retos múltiples, provoca incertidumbre y preocupación respecto al futuro (Báez et al, 2009;Marrón et al, 2013;Ortega et al, 2010). De una u otra forma, quien asume la responsabilidad del cuidado informal en el hogar lo hace con un gran compromiso, mediado por la relación afectiva que lo une a la persona cuidada, cuestionándose pocas veces sobre la propia habilidad de cuidado y disposición para asumir tal responsabilidad (Eterovic et al, 2015;Vaquiro & Stiepovich, 2010).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Caregiver burden and QOL of mothers who care for children with different types of chronic illness had been investigated. Poor QOL had been reported in caregivers of children with tracheostomy (Joseph et al, 2014), autism spectrum disorder (Cadman et al, 2012;Vohra et al, 2013;Miranda et al, 2015), sickle cell disease (van den Tweel et al, 2008), cerebral palsy (Marron et al, 2013) and brain damage (Chronister et al, 2016). Mothers who care for children with a chronic illness were found to have a higher level of anxiety and depression (Özkaya et al 2010), and disrupted sleep patterns that can influence the mood, and, motor and cognitive functioning (Meltzer and Mindell 2006;van den Tweel et al 2008).…”
Section: Qol Of Working Women In Generalmentioning
confidence: 99%